Plaid, Airscarf, or PDK? - Naming Product Features in Online Configurators - Johanna Hasenmaile-Aspin (Marketing Review St.Gallen, 2022)
Product feature names in the automotive industry are becoming more sophisticated, more acronymic, and less descriptive. Along with a categorization of feature names, insights from 26 qualitative consumer interviews, and two online studies, this paper outlines the qualities that feature names should exhibit (regardless of industry) to be perceived as useful by consumers.
Keywords: 650